Designing a contextualized food-based strategy to improve the dietary diversity of children in rural farming households in Central Uganda - Nabuuma, Deborah; Ekesa, Beatrice; Faber, Mieke; Mbhenyane, Xikombiso (SAGE Publications, 2024)
Background: Food-based strategies have a high potential of improving the diet quality and reducing the prevalence of nutrient deficiencies in agriculture-dependent communities. Their design is however complex with trade-offs that are rarely systematically presented to allow replication and efficient contextualization. Objective: The systematic design of a food-based strategy to improve the dietary diversity of children in rural farming communities in Uganda. Methods: The intervention mapping protocol was used to provide a systematic approach to developing theory-based and evidence-based intervention methods and strategy. Results: The priority behavioral and environmental determinants identified were related to food production, consumption, and efficacy while the personal determinants focused on knowledge, skills, self-efficacy, attitude, and outcome expectations. The aim of the resulting strategy was set to improve the availability, accessibility, and consumption of diverse foods, with a particular focus on production diversity, production practices, market access, and market diversity. Behaviour change methods were selected to enhance ability and self-efficacy, strategic goal setting, and provision of feedback. The strategy focused on household groups for learning, demonstration, practice, and social support. The validation showed that the determinants and actors incorporated in the strategy were important and relevant for improving the productivity, food availability, dietary diversity, livelihoods, and health of rural farming households and communities. Conclusion: Application of the protocol yielded a contextualized food-based strategy that can be adjusted for use in other smallholder contexts in developing countries by piloting implementation plans based on the strategy; reassessing the key determinants and implementing the revised strategy; or replicating the whole design process.